Torsed wandering spleen as a cause of recurrent abdominal pain in a child - Tang, Peng Hui; Anithaa Tangaperumal; Nur Aini Ahmad; Mughni Bahari; Aung Mra; Teh, Yong Guang (Elsevier, 2022)
Wandering spleen is an uncommon cause of acute abdomen in children. Diagnosis of this condition is challenging due to its non-specific symptoms, varying intensity and protracted history of presentation. Radiographs and ultrasound imaging provide rapid and reliable means to diagnose this condition without exposure to excessive radiation. We present a case of a torsed wandering spleen in a child with recurrent abdominal pain. We highlight the role of imaging in identifying salient radiographic and sonographic signs for diagnosis.